2009
DOI: 10.4103/0301-4738.57143
|View full text |Cite
|
Sign up to set email alerts
|

Serum cortisol and testosterone levels in idiopathic central serous chorioretinopathy

Abstract: Context:The preferential occurrence of idiopathic central serous chorioretinopathy (ICSC) in males with a typical Type A personality and behavior and a relative absence in females is a possible indicator towards the role of serum cortisol and /or the male sex hormone testosterone.Aims:To study levels of cortisol and testosterone in ICSC.Settings and Design:Case-control study in a tertiary care teaching hospital.Materials and Methods:The study was conducted on 23 cases of ICSC. Twelve patients with unilateral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 22 publications
3
67
0
2
Order By: Relevance
“…Many studies have demonstrated that CSs are a risk factor for acute CSCR [2][3][4][5]. CSs can damage the retina pigment epithelium (RPE) or the tight connection between the retina pigment epithelium (RPE) cells and delay RPE healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated that CSs are a risk factor for acute CSCR [2][3][4][5]. CSs can damage the retina pigment epithelium (RPE) or the tight connection between the retina pigment epithelium (RPE) cells and delay RPE healing.…”
Section: Discussionmentioning
confidence: 99%
“…The etiopathogenesis of CSCR has not been fully elucidated but there are some well-defined risk factors that cause the disorder. These include type A personality, pregnancy, systemic corticosteroid (CS) use and Cushing syndrome [2,3]. There is increased CS in the body in all these conditions and many studies have indicated a relationship between CSs and CSCR pathogenesis [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been associated with type-A personality, elevated endogenous cortisol and corticosteroid therapy in various forms [1,5,6]. The main symptoms range from acute loss of vision to metamorphopsia and scotomas [1][2][3][4][5][6]. We report the case of a young female patient who developed acute CSR without recognisable risk factors.…”
Section: Introductionmentioning
confidence: 97%
“…CSR typically affects young and middle-aged adults (between ages 20 and 40 years) with men being affected more commonly than women by approximately 10 to one [1][2][3][4][5]. It has been associated with type-A personality, elevated endogenous cortisol and corticosteroid therapy in various forms [1,5,6].…”
Section: Introductionmentioning
confidence: 99%